Gingival Enlargement in Patients who Have Undergone Renal Transplants: A Meta-Analysis - Serindere, Gozde; Ozveren, Neslihan (Journal of Dentistry Indonesia, 2018)
Severe gingival enlargement (GE) is one of the most commonly observed adverse effects in patients who have undergone renal transplants due to the use of cyclosporine A. Objectives: We aimed to gain more insight into the prevalence of GE in patients with renal transplants. Methods: We searched the PubMed and Web of Science databases for relevant studies from January 1990 to January 2018. Using random effects models, we calculated summary incidence rates and 95% confidence intervals (CIs). Results: A total of 595 patients from 10 studies were included. Patients using cyclosporine A with or without any other drugs had a 62.6% (95% CI, 41.9%–79.5%) incidence of GE. Subgroup analysis according to diagnostic criteria showed that the incidence of GE was lower when using well-defined diagnostic criteria or scoring system. The incidence of GE was 88.2% (95% CI, 80.9%–93.0%) in patients using cyclosporine A with nifedipine. Cyclosporine A without nifedipine was associated with a significantly decreased risk of GE incidence when compared with the combination of cyclosporine A and nifedipine (odds ratio: 0.198; 95% CI, 0.083–0.473; P < 0.001). Conclusions: It is important for all clinicians to know the effects of the aforementioned drugs and the treatment options.